Association between lipid-lowering drugs and allergic diseases: A Mendelian randomization study - Yinsong Xu, MM; Yuanzhi Li, MD (World Allergy Organization Journal, 2024)
Background: Several observational studies suggest a possible link between lipid-lowering drugs and allergic diseases. However, inferring causality from these studies can be challenging due to issues such as bias, reverse causation, and residual confounding. To investigate the potential causal effect of lipid-lowering drugs, proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitors and 3-hydroxy-3-methyl-glutaryl-coenzyme A reductase (HMGCR) inhibitors, on allergic diseases (allergic asthma, allergic conjunctivitis, atopic dermatitis, allergic rhinitis, and allergic urticaria), we performed a Mendelian randomization (MR)-based study. Methods: We employed MR and summary-data-based MR (SMR), analyzing genome-wide association study (GWAS) data from people of European descent. Single nucleotide polymorphisms (SNPs) were employed as instrumental variables. We selected 2 types of genetic measures to represent the impact of lipid-lowering drugs, including genetic variants near or within drug target genes correlated with low-density lipoprotein cholesterol (LDL-C), and expression quantitative trait loci of drug target genes. The inverse-variance weighted (IVW)-MR approach was the primary utilized MR method, while sensitivity analyses were used to test the robustness of the results. We used SMR analysis as a supplementary analytical method, applying the heterogeneity in dependent instruments (HEIDI) test to assess if the observed correlation between gene expression and outcome was due to a linkage situation. Results: The IVW-MR analysis revealed significant evidence for an association between PCSK9-mediated LDL-C reduction and a decrease in the risk of allergic asthma (odds ratio [OR] = 1.31, 95% confidence interval [CI] = 1.11–1.56; P < 0.01). Likewise, SMR analysis discovered an augmented expression of PCSK9 being linked with a heightened susceptibility to allergic asthma (OR = 1.21, 95% CI = 1.03–1.43; P = 0.02). No consistent evidence was found for other associations in either analysis. Conclusion: Our findings support a potential causal relationship between PCSK9 activity and an increased risk of allergic asthma. Thus, PCSK9 inhibitors, which reduce PCSK9 activity, might be considered a priority in future clinical trials investigating drugs for allergic asthma prevention or treatment.